An evaluation study of secondary school principal?s instructional program management performance as perceived by teachers in Rivers States, Nigeria - Peretomode, Victor F.; Agre, Uzo M.
The purpose of this study is to investigate the instructional leadership performance of secondary school principals in River State of Nigeria on certain variables using the perceptions of teachers. More specifically, the study is designed to examine whether or not principals are currently performing well in overall management of instructional programmes in the River States secondary school system.
Keywords: High school principals -- Nigeria -- River States; Teacher-principal relationships -- Nigeria -- River States; School management and organization -- Nigeria -- River States